Modulation of Angiogenesis-Related Biomarkers in Brain and Myocardial Tissues by Exercise and Carnosine: An ELISA-Based Analysis of VEGF-A, HIF-1?, Ang-1, MMP-9, and Anti-Angiogenic Factors - Bolat, Husne; Akbulut, Taner; Cinar, Vedat; Avcu, Emsal Cagla; Yasul, Yavuz; Bozbay, Kenan; Aydin, Suleyman (Wiley-V C H Verlag Gmbh, 2025)
This study explored the impact of aerobic and anaerobic exercise, combined with carnosine supplementation, on angiogenesis-related biomarkers in cardiac and cerebral tissues. Forty-five male Sprague-Dawley rats were randomly allocated to seven groups: control (C), sham (S), carnosine (Cz), aerobic exercise (AE), anaerobic exercise (AnE), AE + Cz, and AnE + Cz. Exercise protocols were performed 5 days per week for 5 weeks (aerobic: 15 m/min; anaerobic: 25 m/min), while carnosine was administered orally (100 mg/kg/day). Biomarker levels of VEGF-A, HIF-1 alpha, Ang-1, MMP-9, tumstatin, and endostatin were measured using ELISA, and data were analyzed by ANOVA, Pearson correlation, PCA, and hierarchical clustering. The myocardial tissue revealed that VEGF-A, HIF-1 alpha, and Ang-1 significantly increased in exercise and combined groups (p < 0.05), with AE + Cz showing the highest VEGF-A and AnE + Cz the highest HIF-1 alpha. The tumstatin and endostatin levels were significantly reduced in AE and AE + Cz groups. The brain tissue indicated that Ang-1 increased, while tumstatin and endostatin consistently decreased across all exercise groups. PCA and clustering analyses revealed a dominant pro-angiogenic profile in AE + Cz and AnE + Cz, whereas C, S, and Cz groups showed anti-angiogenic tendencies. Carnosine supplementation may represent a nutritionally relevant approach to modulate exercise-induced angiogenic adaptations with possible implications for cardiovascular and neurovascular health.
Keywords: Ang-1; carnosine; endostatin; exercise; HIF-1 alpha; MMP-9; tumstatin; VEGF-A